Sentinel lymph node biopsy using single-agent mapping tracer (blue dye) after neoadjuvant chemotherapy in a Brazilian cohort of breast cancer patients. Real world evidence - Resende,Heloisa Magda (2021)
ABSTRACT Purpose To reduce false-negative rates (FNR) in sentinel lymph node biopsy (SLNB) of clinically positive (cN+) axilla in patients undergoing neoadjuvant chemotherapy (NAC). The removal of three or more lymph nodes with dual-tracer mapping including a radioisotope was used. However, in the Brazilian Unified Health System, the radioisotope tracer is not feasible in some hospitals. We conducted a cross-sectional study to evaluate the detection rate of sentinel lymph node (SLN) in patients who converted from cN+ to ycN0 after NAC using blue dye as a single-agent mapping tracer. Methods During the period of March 2018 to September 2019, 34 patients who underwent NAC with cN+ who converted to ycN0 were enrolled in the study. The SLNB was performed using blue dye as a single-agent mapping followed by axillary lymph node dissection (ALND). Results The detection rate of sentinel lymph node was of 85.3%, being SLNB not possible for five patients (14.7%), due to fibrosis. The mean number of removed SLN was 2.5. Conclusions The use of blue dye as a single-agent mapping tracer demonstrated an acceptable detection rate of 85.3%. Although the FNR was possible to be determined, the small sample size might overestimate this rate. The removal of three or more lymph nodes with single-agent mapping tracer might be indicated for breast cancer patients who converted to ycN0 after NAC in the Brazilian health public services, in which radioisotope tracer is not suitable.